The Effect of An Emergency Evacuation on the Spread of COVID19 - Butail, Sachit; Porfiri, Maurizio (Frontiers in Physics, 2021)
In an emergency evacuation, people almost always come in close proximity as they force themselves to leave a built environment under a potential threat. With COVID19, this situation presents yet another challenge: that of getting unintentionally exposed to an infected individual. To assess the epidemiological consequences of an emergency evacuation, we expanded on a popular pedestrian dynamic model to enable social distancing during a normal exit and analyze transmission through respiratory droplets and aerosol. Computer simulations point to a troubling outcome, whereby the benefits of a quick exit could be outweighed by the risk of infection.